Kegiatan Penangkapan Ikan di Suaka Perikanan Sungai Sambujur Daerah Aliran Sungai Barito Bagian Tengah, Kalimantan Selatan - Dadiek Prasetyo (Universitas Gadjah Mada, 2006)
The objectives of this research were to provide data on fishing gears and methods in fisheries reserve of Sungai Sambujur, South kalimantan. Data were collected by purposive sampling survey method. The result showed that there were 6 fishing gears operated in Sungai Sambujur fisheries reserve: hampang, pengilar, lukah, luntak, rengge and kawat. Fishing gear which was able to catch fish with the most variety was hampang, followed by luntak, rengge, lukah, pengilar and kawat. Fish catching season was from May to December and July was a peak of catching season. On the other hand, the height of water level occured from 2 to 7 m.